Znaczenie „doświadczenia hermeneutycznego” w ujęciu H.-G. Gadamera dla edukacji - Teusz , Grażyna (Studia Edukacyjne, 2019)
The aim of the article is to present the meaning and essence of the “hermeneutical experience” in the H.-G. Gadamer’s perspective for the theory and educational practice. The topics address the relationship between pedagogy and philosophy, the presence of philosophical ideas in the reflection on upbringing and the practice of upbringing.